Impact energy absorption capability of thermoplastic commingled composites - Di Benedetto, R. M. [UNESP]; Botelho, E. C. [UNESP]; Gomes, G. F.; Junqueira, D. M.; Ancelotti Junior, A. C. (Elsevier, 2019)
The energy absorption capability of structural thermoplastic composites is governed by the matrix thermal degradation kinetics. This study focuses on the development of a multiple regression model to predict the impact energy absorption of commingled composites considering processing parameters, matrix properties and thermal degradation kinetics. The model has been developed based on the carbon fiber/polyamide 6 commingled composite response on the low velocity impact test. Furthermore, the thermal degradation limits have been provided by the Friedman's isoconversional method and the processing parameters by the Darcy's law. Infrared spectroscopy has been used in order to identify the polyamide type used as matrix. The viscosity behavior of the molten polymer was evaluated by using a torque rheometry. Dynamic mechanical analysis defined the maximum operating temperature of the material and the rubbery plateau zone. The regression model was able to predict the commingled composite impact energy absorption in different temperatures and processing times revealing the response surface associated with the dissipated energy.
Keywords: Commingled composites; Low velocity impact test; Multiple regression model; Thermal degradation kinetics